PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR IPA SISWA KELAS IVSDNEGERI REJOWINANGUN IYOGYAKARTA - Agesy, Famela Indah; Budhi, Widodo; Utaminingsih, Retno (Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of this research was to determine the differences in students learning result between who apply inquiry learning models and expository models. This research is experimental research. The research design used is a nonequivalent control group. The sampling technique is done by random sampling. The analysis prerequisite test is the distribution normality test and variance homogeneity. Based on the results of data analysis, obtained tcount = 2.332 with p = 0.0024 <0.01, so the hypothesis is accepted. Thus it can be concluded that there are very significant student differences learning result in grade IV SD Negeri Rejowinangun I Yogyakarta between those who apply the inquiry learning model and the expository learning model. The mean score of the science learning result of students who applied the inquiry learning model 16.03 was higher than the expository learning model 12.74. It means that there is an influence of the inquiry learning model on the learning result of Natural Sciences students in grade IV SD Negeri Rejowinangun I Yogyakarta.